2006
DOI: 10.1039/b600056h
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic interactions in cations and their importance in biology and chemistry

Abstract: Electrostatic effects exert strongly stabilizing influences on cations, in many cases controlling the conformational preferences of these cations. The lowest energy conformers are ones where the positive charge is brought closest to substituents bearing partial negative charges. These conformational biases, along with stereoelectronic effects, can control the stereoselectivity of reactions involving carbocationic intermediates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
116
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(122 citation statements)
references
References 90 publications
6
116
0
Order By: Relevance
“…[18] A consequence of the above is that a glycosyl donor may change conformation during a reaction adopting the more reactive conformer (Scheme 4). Woerpel and co-workers have in fact shown this to be the case, [19] pyranosyl oxocarbenium ions with 4-methoxy or 4-methyl substituents react in Cglycosylations with opposite facial selectivity because the former prefer a half-chair conformation with the 4-substituent axial and the latter a half chair with an equatorial substituent, [20] and the nucleophile attacks axially on the ions. [19,20] It has been suggested that this is why glycosylation with mannuronate esters gives the b product.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18] A consequence of the above is that a glycosyl donor may change conformation during a reaction adopting the more reactive conformer (Scheme 4). Woerpel and co-workers have in fact shown this to be the case, [19] pyranosyl oxocarbenium ions with 4-methoxy or 4-methyl substituents react in Cglycosylations with opposite facial selectivity because the former prefer a half-chair conformation with the 4-substituent axial and the latter a half chair with an equatorial substituent, [20] and the nucleophile attacks axially on the ions. [19,20] It has been suggested that this is why glycosylation with mannuronate esters gives the b product.…”
Section: Introductionmentioning
confidence: 99%
“…Woerpel and co-workers have in fact shown this to be the case, [19] pyranosyl oxocarbenium ions with 4-methoxy or 4-methyl substituents react in Cglycosylations with opposite facial selectivity because the former prefer a half-chair conformation with the 4-substituent axial and the latter a half chair with an equatorial substituent, [20] and the nucleophile attacks axially on the ions. [19,20] It has been suggested that this is why glycosylation with mannuronate esters gives the b product. The intermediate adopts the half-chair conformation with a maximal number of axial substituents, which, in this case, upon axial attack gives the observed b anomer.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] It emerges that organic cations containing oxygen and fluorine find stabilization through such interactions: polarized C À OH and C À F bonds orient towards charged centers when the molecular conformation allows. This effect has been particularly noted by Snyder, Lankin, and co-workers, who reported the conformational preferences of 3-fluoropiperidinium (1) and related ring systems, such as 3-fluoro-N,N-dimethylpiperidinium (2).…”
mentioning
confidence: 99%
“…In the case of 10, the chemical shifts of both sets of methylene protons in the 2-fluoroethyl moiety are almost identical. This situation gives rise to a second-order 1 H and 19 F NMR spectrum, which could be accurately simulated (Bruker Topspin/Daisy) with average 3 J HF and 3…”
mentioning
confidence: 99%
“…Differences in reactivity of mannopyranosyl and glucopyranosyl oxacarbenium ions have also been commented recently by Lucero and Woerpel,14 in the context of a broader investigation into the synthesis of C-glycosides and the influence of substituents on the stereoselectivity of oxacarbenium ion trapping. 15 In the absence of a conformationally restricting group, such as the benzylidene acetal, these authors considered the tetra-O-benzylmannopyranosyl cation to exist predominantly in the 3 H 4 conformer but to react via the less populated 4 H 3 form, in a typical Curtin-Hammett kinetic scheme to afford the α-C-glycosides in high yield. The α-selective C-glycosylation of the tetra-O-benzylglucopyranosyl cation was also considered to take place through the 4 H 3 conformer.…”
Section: Introductionmentioning
confidence: 99%